Creating Sustainable Food Markets (A Case Study of Urban Consumers’ Camel Milk Consumption in Khartoum – Sudan) - Fawi, Nahid, M. T.; Ahmed, Hadeel, M. A. (Journal of Veterinary Medicine and Animal Production, 2021)
This research aimed at elaborating consumer oriented scientifically based marketing strategies of camel milk ; based on strong market research data as a key factor for opening marketing opportunities to camel milk producers and creating consumer awareness about the nutritional and health benefits of camel milk. The study was performed in Khartoum North during the period 2014- 2015. A cross-sectional scientifically structured questionnaire based mainly on Likert scale was conducted where the study was based on primary data collected from the selected sample. Urban Camel milk consumers in Khartoum North were the population of this study. Sampling was limited to accessible consumers in Dairy products Distribution centers and five camel dairy farms found in Khartoum north the sampling included 60 consumers. Data was analyzed using the Statistical Package for Social Sciences (SPSS ver. 13) to obtain the frequency of distributions of the respondents with regard to the variables of the study.The research came to a main conclusion, that there is a high need to facilitate stakeholders support for increased resources for research and development on issues related to the camel industry in Sudan in order to facilitate development of marketing strategies for camel milk in domestic and International markets.